A prospective, controlled study of non-motor effects of subthalamic stimulation in Parkinson's disease: results at the 36-month follow-up. Issue 7 (5th May 2020) - Jost, Stefanie Theresa; Sauerbier, Anna; Visser-Vandewalle, Veerle; Ashkan, Keyoumars; Silverdale, Monty; Evans, Julian; Loehrer, Philipp A; Rizos, Alexandra; Petry-Schmelzer, Jan Niklas; Reker, Paul; Fink, Gereon Rudolf; Franklin, Jeremy; et al.
Abstract : Objective: To examine 36-month effects of bilateral subthalamic nucleus deep brain stimulation (STN-DBS) on non-motor symptoms (NMS) compared with standard-of-care medical treatment (MED) in Parkinson's disease (PD). Methods: Here we report the 36-month follow-up of a prospective, observational, controlled, international multicentre study of the NILS cohort. Assessments included NMSScale (NMSS), PDQuestionnaire-8 (PDQ-8), Scales for Outcomes in PD (SCOPA)-motor examination, -activities of daily living, and -complications, and levodopa equivalent daily dose (LEDD). Propensity score matching resulted in a pseudo-randomised sub-cohort balancing baseline demographic and clinical characteristics between the STN-DBS and MED groups. Within-group longitudinal outcome changes were analysed using Wilcoxon signed-rank and between-group differences of change scores with Mann-Whitney U test. Strength of clinical responses was quantified with Cohen's effect size. In addition, bivariate correlations of change scores were explored. Results: Propensity score matching applied on the cohort of 151 patients (STN-DBS n=67, MED n=84) resulted in a well-balanced sub-cohort including 38 patients per group. After 36 months, STN-DBS significantly improved NMSS, PDQ-8, SCOPA-motor examination and -complications and reduced LEDD. Significant between-group differences, all favouring STN-DBS, were found for NMSS, SCOPA-motor complications, LEDD (large effects), motor examination and PDQ-8 (moderate effects). Furthermore, significant differences were found for the sleep/fatigue, urinary (large effects) and miscellaneous NMSS domains (moderate effects). NMSS total and PDQ-8 change scores correlated significantly. Conclusions: This study provides Class IIb evidence for beneficial effects of STN-DBS on NMS at 36-month follow-up which also correlated with quality of life improvements. This highlights the importance of NMS for DBS outcomes assessments.